Abundance of Common Aerobic Anoxygenic Phototrophic Bacteria in a Coastal Aquaculture Area - Sato-Takabe, Yuki; Nakao, Hironori; Kataoka, Takafumi; Yokokawa, Taichi; Hamasaki, Koji; Ohta, Kohei; Suzuki, Satoru (Frontiers in Microbiology, 2016)
Aerobic anoxygenic phototrophic bacteria (AAnPB) rely on not only heterotrophic but also phototrophic energy gain. AAnPB are known to have high abundance in oligotrophic waters and are the major portion of the bacterial carbon stock in the environment. In a yearlong study in an aquaculture area in the Uwa Sea, Japan, AAnPB, accounted for 4.7 to 24% of the total bacteria by count. Since the cell volume of AAnPB is 2.23 ± 0.674 times larger than the mean for total bacteria, AAnPB biomass is estimated to account for 10 to 53% of the total bacterial assemblage. By examining pufM gene sequence, a common phylogenetic AAnPB species was found in all sampling sites through the year. The common species and other season-specific species were phylogenetically close to unculturable clones recorded in the Sargasso Sea and Pacific Ocean. The present study suggests that the common species may be a cosmopolitan species with worldwide distribution that is abundant not only in the oligotrophic open ocean but also in eutrophic aquaculture areas.